The Influence of Social Identity and Attitudes Toward Anti-Smoking Campaigns on Smokers’ Self-stigma - Daffa Tiara Kurnia Prastiwi (Kajian Psikologi dan Kesehatan Mental, 2025)
Purpose: This study aims to determine the influence of Social Identity and Attitudes towards the Anti-Smoking Campaign on Smoker Self-stigma. Methodology: The research was conducted using a quantitative approach with the population in this study being smokers. The sampling technique used was Quota Sampling with the sample in this study amounting to 320 respondents with the main criteria being 18-40. The data analysis technique used is multiple linear regression analysis. Results: The analysis results show the calculated F value is 24,706 with a probability of 0.000 (p < 0.01). Next, in the first minor hypothesis, the value is p = 0.000 (p < 0.01). In the second minor hypothesis, the results of multiple linear regression analysis obtained a value of p = 0.001 (p < 0.01). Conclusion:  In conclusion, social identity and attitudes towards anti-smoking campaigns together have an influence on self-stigma. In the first minor hypothesis, there is a very significant negative influence (in the opposite direction) between self-stigma and social identity. In the second minor hypothesis, there is a very significant negative influence (in the opposite direction) between self-stigma and attitudes towards anti-smoking campaigns. Limitations: Anti-smoking campaigns and social identities may differentially contribute to each dimension of stigma, which in turn leads to different consequences. Contribution: The finding that social identity actually has a negative relationship with self-stigma adds to the literature by suggesting that group identification can serve as a protective mechanism that reduces feelings of shame and alienation, particularly in collectivistic societies that emphasize values ??of togetherness and social solidarity.